The effect of good corporate governance on financial distress - Indrati, Menik; Handayani, Rafika (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of good corporate governance on financial distress. Corporate governance (independent boards of commissioners, blockholder ownership, CEO-chair duality and board ownership) and financial hardship are being studied on firms listed on the Indonesian Stock Exchange between 2017 and 2019, according to a study. Purposive sampling was utilized by the researchers in this study to collect their data. Information about financial statements and corporate annual reports may be found at www.idxco.in, the primary source. This research includes 30 different firms. Statistical methods such as logistic regression analysis were employed in our investigation. The audit committee, the ceo-chair duality, board ownership, or the independent board of commissioners had no influence on the organization's financial troubles.